Cotton research towards sufficiency to Indian textile industry - Rajendran, T P; Venugopalan, M V; Praharaj, C S (The Indian Journal of Agricultural Sciences, 2005)
India has been the traditional home of cotton and cotton textiles.The domestication of the cotton plant for commercial cultivation for clothing as well as for other forms of human utilization is considered to have begun from Harappa civilisation in this sub-continent using diploid or Asiatic cottons (Gossypium herbaceum and G.arboreum). Indian economy has been consistently influenced and boosted by cotton through its production and processing sectors and by generating direct and indirect employment to more than 8 million people and by annual addition to national wealth through export earning of over Rs 45 000 crores (Kairon et al. 1998). Cotton is the most vital crop of commerce, popularly known as the ’White Gold’. In India, all the 4 cultivated cotton species, viz G. arboreum, G.herbaceum, G.hirsutum and G. barbadense are grown commercially. The diploid cottons (G. arboreum and G. herbaceum) are mainly cultivated in dryland tracts though Bengal desi is grown under irrigated conditions in the northern states. G. hirsutum is known as the American cotton and most popular varieties and hybrids now under cultivation belong to this group. G. barbadense is popularly known as the Egyptian cotton and is grown in small area in India